Fetal Programming of the Human Brain: Is there a Link with Insurgence of Neurodegenerative Disorders in Adulthood? - Faa, G.; Marcialis, MA.; Ravarino, A.; Piras, M.; Pintus, MC.; Fanos, V. (Current Medicinal Chemistry, 2014)
In recent years, evidence is growing on the role played by gestational factors in shaping brain development and on the influence of intrauterine experiences on later development of neurodegenerative diseases including Parkinson’s (PD) and Alzheimer’s disease (AD). The nine months of intrauterine development and the first three years of postnatal life are appearing to be extremely critical for making connections among neurons and among neuronal and glial cells that will shape a lifetime of experience. Here, the multiple epigenetic factors acting during gestation - including maternal diet, malnutrition, stress, hypertension, maternal diabetes, fetal hypoxia, prematurity, low birth weight, prenatal infection, intrauterine growth restriction, drugs administered to the mother or to the baby – are reported, and their ability to modulate brain development, resulting in interindividual variability in the total neuronal and glial burden at birth is discussed. Data from recent literature suggest that prevention of neurodegeneration should be identified as the one method to halt the diffusion of neurodegenerative diseases. The “two hits” hypothesis, first introduced for PD and successfully applied to AD and other neurodegenerative human pathologies, should focus our attention on a peculiar period of our life: the intrauterine and perinatal periods. The first hit to our nervous system occurs early in life, determining a PD or AD imprinting to our brain that will condition our resistance or, alternatively, our susceptibility to develop a neurodegenerative disease later in life. In conclusion, how early life events contribute to late-life development of adult neurodegenerative diseases, including PD and AD, is emerging as a new fascinating research focus. This assumption implies that research on prevention of neurodegenerative diseases should center on events taking place early in life, during gestation and in the perinatal periods, thus presenting a new challenge to perinatologists: the prevention of neurodegenerative human diseases.
Keywords: perinatal programming